2010
DOI: 10.1007/s10517-010-1009-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Indoleamine-2,3-Dioxygenase 1-Methyl-D-Tryptophan Can Stimulate the Growth of Immunogenic Tumors

Abstract: We studied the effect of 1-methyl-D-tryptophan, an inhibitor of indoleamine-2,3-dioxygenase, on the growth of transplanted hepatocarcinoma-29 in C3HA mice. Hepatocarcinoma-29 transplanted into the thigh muscles undergoes immunological rejection in more than 50% non-syngeneic recipients. Chronic local administration of 1-methyl-D-tryptophan promotes progressive growth of the tumor in recipient mice leading to 100% animal death. The stimulating effect of 1-methyl-D-tryptophan on tumor growth is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It was previously shown that the effects of IDO inhibitors can be opposite at various stages of interactions between the tumor and the body. This manifests in suppression of the growth of formed tumors and stimulation of the growth during fi rst contact of tumor cells and the organism [2,3]. To a certain degree, it is applicable to clinical situations, where new immunogenic clone can be developed on the basis of already formed tumors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that the effects of IDO inhibitors can be opposite at various stages of interactions between the tumor and the body. This manifests in suppression of the growth of formed tumors and stimulation of the growth during fi rst contact of tumor cells and the organism [2,3]. To a certain degree, it is applicable to clinical situations, where new immunogenic clone can be developed on the basis of already formed tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that IDO inhibitors affected tumor growth in mice in the non-syngeneic system [1][2][3], which prompted us to continue these investigations on the models approximating clinical cases, e.g. on a tumor with proven immunogenicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent clinical trials have evaluated the response of patients to 1MDT (clinical trial NCT01302821, details at http://clinicaltrials.gov/). However, controversies exist, and the use of 1MDT promoted the growth of hepatocarcinoma in recipient mice leading to death [53]. Some have suggested these results are Numerous studies have examined the molecular regulation of HLA-G gene expression.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%